On some Security aspect of HPC Environment (International Journal of Engineering and Computer Science, 2014)
HPC (High Performance Computing) or simply, supercomputer has evolved to become one of the most exciting and challenging areas in the field of information technology & computer science. In this paper, we have discussed on issues related to security of data and information in respect with HPC environment. Data and information are valuable and deserve a proper security and safety. The purpose of this paper is to present some practical security issues related to HPC or super-computing Environment. Based on our literature survey on issues related to security requirements of HPC, we have observed that some existing security technologies are already existing, which are being used in HPC. But, our observation also leads to a conclusion that improvements are required and the existing techniques are not enough. Further, we have discussed some of the key issues relating to this context and made an approach to find an appropriate solution using RSA encryption and decryption algorithm. We have studied the concept of parallelism in RSA environment and found that it produces a better and efficient computation result in respect of space and time complexity. In the later part of the paper, we have proposed a modified RSA algorithmic technique by attaching a large prime number generator algorithm to make the encryption decryption technique more appropriate for our HPC environment [20].